The idealogical meaning of mass-media and their critical review in covering of the migration crisis’s theme - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article examines the ideological context of the modern media functioning, and concretizes the ambiguous role of the media in covering the theme of global migration crisis. A critical review of media messages within this theme corresponds with the educational goal of media education and media philosophy.